The Complete CSS Flexbox Guide with a Complete Project [Updated for 2021] - Sadek, Ahmed (Packt Publishing, 2021)
Learn how to build advanced responsive layouts quickly and easily with minimal code using flexbox About This Video Gain a solid understanding of flexbox and its properties Learn how to use flexbox to center elements vertically Get ready to build impressive photo galleries using flexbox In Detail Do you want to create complex website layouts easily and quickly with just simple lines of code? This course will help you to create those complex website layouts with ease using the magic of flexbox. You will start this course by creating your first flexbox container to understand how flexbox works. Next, you will learn how to control the alignment of elements using the CSS flexbox. Moving along, you will grasp techniques to control the size of elements and to build basic and advanced menus using flexbox. Toward the end, you will learn to build a website with advanced responsive layouts, such as Holy Grail, equal columns layout, and horizontal masonry. By the end of this course, you will be able to create real-world responsive website layouts using flexbox.